Records of threatened bird and mammal species in Mato Grosso do Sul State, Brazil - Sylvia Torrecilha; Jose Manuel Ochoa-Quintero; Rudi Ricardo Laps; Danilo Bandini Ribeiro (Data in Brief, 2018)
We conducted a detailed review of threatened bird and mammal occurrence records obtained from surveys across Mato Grosso do Sul, midwestern region of Brazil which has an extent of 357,145 km2, aiming to support environmental and biodiversity conservation initiatives, as strategic plans to protect threatened species in this region. We included all records of species categorized as threatened by the Brazilian and global red list of threatened species. We collected 760 records of threatened birds and mammals in Mato Grosso do Sul State, with 319 records of 40 bird’s species and 441 records of 24 mammal’s species. The status of the 40 bird species under de Brazilian threat category were as follow: 1 Critically Threatened (CR), 6 Endangered (EN), 11 Vulnerable (VU), 11 Near Threatened (NT), and 11 species only in the IUCN red list. Under the IUCN category for the bird´s species, were as follow: 3 EN, 13 VU, 18 NT, 5 Least Concern (LC) and 1 taxon has not yet been assessed for the IUCN Red List. Regarding mammal’s species under the Brazilian threat category were as follow: 2 EN, 18 VU, 2 NT and 1 only in the IUCN red list. Under the IUCN status the species ranged from 2 EN, 6 VU, 10 NT, and 6 LC. Each record identified corresponds to the existence of at least one occurrence of threatened birds or mammals in a particular region. The records of threatened species belongs to the three biomes in the state: 269 mammal’s records and 147 bird’s records from Cerrado (Neotropical Savanna) biome, 117 mammal’s records and 162 bird’s records from Pantanal (Wetland) biome, and 55 mammal’s records and 10 bird’s records from Atlantic Forest biome. In addition, we also included in the dataset environmental information where each record was obtained. Supplementary Files 1- Records of Threatened Mammals_MS_Brazil and Supplementary File 2. Records of Threatened Birds of_MS_Brazil Keywords: Threatened species, Protected areas, Database, Brazil